UKURAN PERTAMA KALI TERTANGKAP, UKURAN PERTAMA KALI MATANG GONAD DAN STATUS PENGUSAHAAN Selar boops DI PERAIRAN BITUNG - Saranga, Rudi; Simau, Silvester; Kalesaran, Jerry (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2019)
This research was carried out because the information related to the size of fish capture and the status of exploiting S. boops was still very little, especially in the waters around Bitung. The appropriate size of capture and exploitation status can be used as a reference to assess whether the utilization of S. boops resources in the waters around Bitung is in accordance with the sustainable management guidelines for fish resources. This study aims (1) to get the size of the first caught fish (Lc); (2) get the size of fish first cooked gonad (Lm); (3) obtain S. boops business status. The sampling of fish was obtained from the Bitung coastal fishermen who landed his catch at the Bitung Ocean Port. Retrieval of fish sample data was carried out from February 2016 to January 2017 with a total samples 1,659 using the survey method. The results showed that the size of first captured 15.10 cm FL while the size of the first matured obtained 16.30 cm FL. The status of exploitation based on the comparison of Lc and Lm parameters that percentage of matured and the SPR value categorized as overfishing.